2009
DOI: 10.1186/1471-2148-9-240
|View full text |Cite
|
Sign up to set email alerts
|

An EST screen from the annelid Pomatoceros lamarckii reveals patterns of gene loss and gain in animals

Abstract: BackgroundSince the drastic reorganisation of the phylogeny of the animal kingdom into three major clades of bilaterians; Ecdysozoa, Lophotrochozoa and Deuterostomia, it became glaringly obvious that the selection of model systems with extensive molecular resources was heavily biased towards only two of these three clades, namely the Ecdysozoa and Deuterostomia. Increasing efforts have been put towards redressing this imbalance in recent years, and one of the principal phyla in the vanguard of this endeavour i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 54 publications
3
24
1
Order By: Relevance
“…While similar peptides (including –RLamides, -SIamides and -FVRIamides) have been described in other invertebrate phyla, including Annelida and Mollusca (Chen et al, 1995; Pedder et al, 2001; El Filali et al, 2006; Jekely et al, 2008; Takahashi et al, 2009), we could find no evidence for the presence of similar peptides in vertebrate host organisms. The NPP-1-like peptides reported here thus represent a group of novel helminth neuropeptides which, if they are absent from host species, and are functionally conserved across helminths, could represent particularly promising avenues for drug development.…”
Section: Discussioncontrasting
confidence: 79%
“…While similar peptides (including –RLamides, -SIamides and -FVRIamides) have been described in other invertebrate phyla, including Annelida and Mollusca (Chen et al, 1995; Pedder et al, 2001; El Filali et al, 2006; Jekely et al, 2008; Takahashi et al, 2009), we could find no evidence for the presence of similar peptides in vertebrate host organisms. The NPP-1-like peptides reported here thus represent a group of novel helminth neuropeptides which, if they are absent from host species, and are functionally conserved across helminths, could represent particularly promising avenues for drug development.…”
Section: Discussioncontrasting
confidence: 79%
“…This conservative nature of annelids, or at least of the polychaete annelids examined, also extends to the less divergent nature of their gene sequences (Fig. 5B) and the retention of more ancestral gene organisations than are found in traditional invertebrate models Takahashi et al, 2009). A greater proportion of the introns that were present in the protostome-deuterostome ancestor (PDA; sometimes called the Urbilaterian ancestor) have been retained in P. dumerilii than in most other invertebrates examined .…”
Section: Insights Into Evolutionary Developmental Genomicsmentioning
confidence: 64%
“…The general picture is one of a greater degree of retention of genes in annelids that were present in the ancestral bilaterian than can be found in ecdysozoan model systems, such as fruit flies and nematodes (e.g. Prud'homme et al, 2002;Tessmar-Raible et al, 2007;Simionato et al, 2008;Takahashi et al, 2009;Cho et al, 2010;Shimeld et al, 2010) (Fig. 5A).…”
Section: Insights Into Evolutionary Developmental Genomicsmentioning
confidence: 99%
“…These results suggest that Hydroides genome content has not evolved as quickly as the fruit fly and nematode genomes. Consistent with these findings, other annelids were found to possess relatively slowly evolving genomes (43,44), and D. melanogaster and C. elegans are documented to possess more derived genomes with extensive gene loss and higher rates of molecular evolution (45,46). Studying mechanisms that mediate bacteria-induced metamorphosis in Hydroides might provide a framework to understand bacteria-animal interactions in diverse animals.…”
Section: Resultsmentioning
confidence: 63%
“…S1). Previous studies also reported relatively slow evolutionary rates of annelids compared with the model ecdysozoans D. melanogaster and C. elegans (43)(44)(45)(46), suggesting that annelids might share more ancestral characteristics with distantly related model animals. Mechanisms underpinning the metamorphic response of Hydroides to bacterial inducers might therefore have conserved features present in other metazoans and serve as an example of how bacteria impact the development of an animal.…”
Section: Discussionmentioning
confidence: 94%